The Effect of Globalization on the Ideology of Pancasila - Kurniasih, Ria (Universitas Negeri Semarang, 2016)
Pancasila is often seen as an ideology that deals with global ideologies, such as capitalism and liberalism. The Pancasila that was built was for the common welfare and social justice for all Indonesian people. On the other hand, we live in a globalization that is full of laws and rules of capitalism, free and open markets. We must remain firm and strong in our stance, that we will continue to dedicate all of these things to the common good, to social justice. An intelligent nation in the era of globalization, is not a nation that continues to complain, give up, and get angry, but a nation that is able to drain the sources of prosperity available in the global arena. We all use technology, capital or information properly to improve our welfare and interests. Don't want to be the loser. Let's be winners in this globalization. Globalization is an era of rapid changes that contain positive things, but also brings negative aspects for the Indonesian people. The Indonesian people must be good at seizing and taking advantage of opportunities from the positive aspects and still standing on the values that have been pledged, defended, and upheld. Facing globalization, the Indonesian nation must be able to stand up by having sovereignty in the political field, independence in the economy, personality in culture, and having strong resilience in national security. More than that, we must continue to strengthen our identity as Pancasilaists who uphold the 1945 Constitution of the Republic of Indonesia and strengthen the establishment of the Unitary State of the Republic of Indonesia. Every citizen is obliged to defend his country so that the survival of his nation is maintained. To defend the country is largely determined by the attitudes and behavior of every citizen. If citizens are active and care about the progress of their nation, the survival of the nation will be maintained. It is better if citizens do not care about the problems facing their nation, the survival of the nation will be threatened and sooner or later the state will dissolve.